PENGGUNAAN MEDIA POHON NORMA BERBASIS PROBLEM BASED LEARNING UNTUK MEMBANTU PEMAHAMAN MATERI NORMA PADA SISWA SEKOLAH DASAR : PENGGUNAAN MEDIA POHON NORMA BERBASIS PROBLEM BASED LEARNING UNTUK MEMBANTU PEMAHAMAN MATERI NORMA PADA SISWA SEKOLAH DASAR - Pasha afriana; Putri Agustina; Susilo Tri Widodo; Niken Saraswati (STKIP Subang, 2025)
Although the teaching of norms in Civic Education has received increasing scholarly attention, research addressing the integration of concrete visual media with Problem Based Learning (PBL) to overcome students’ conceptual difficulties remains limited. This study aims to evaluate the effectiveness of the “Norm Tree Media” combined with PBL in enhancing elementary students’ understanding of various types of norms. Employing a descriptive qualitative approach with a single-case study design, this research involved one Grade 5 teacher selected through purposive sampling. Data were gathered through semi-structured interviews, classroom observations, and document analysis, and then analyzed using thematic analysis. The findings reveal that the integration of concrete media and PBL encourages students to actively analyze real-life situations, differentiate types of norms, and connect abstract concepts with their daily experiences. Nevertheless, several students continued to struggle in distinguishing norm categories with similar contextual characteristics, requiring additional scaffolding from the teacher. This study contributes to the theoretical development of constructivist learning and broadens insights into contextual practices in Civic Education. The study concludes that concrete media combined with problem-based learning activities plays a crucial role in strengthening students’ conceptual understanding and recommends that teachers adopt integrative and contextual learning strategies. The implications of the research include contributions to Civic Education pedagogy and practical recommendations for schools to optimize the use of concrete media and problemsolving–based learning. Future research is encouraged to examine the effectiveness of similar media across diverse student groups and learning contexts.